The C3PDR Learning Model to Increase Conceptual Understanding and Creative Thinking Skills of Senior High School Students - Emilia Julfitri; Shelly Efwinda; Zulkarnaen Zulkarnaen (Universitas Lambung Mangkurat, 2020)
The C3PDR Learning Model was designed to increase student creativity in science. This study aimed to determine the effect of C3PDR learning model on improving conceptual understanding and creative thinking skills of senior high school students on sound waves topic. This study used a Quasi-Experimental Method and One-Group Pretest-Posttest Design. The sample in this study was 32 students of the eleventh-grade student in the 2017/2018 academic year from one of senior high school in Samarinda, selected by purposive sampling. Data collection used Test Techniques. The instrument used Essay Questions. Essay questions indicators to determine the understanding of physics concepts were interpreting, clarifying, comparing, summarizing, and inferring. Essay questions indicators to determine students' creative thinking skills were Asking Questions, Guessing the Causes, Guessing the Cause of an Occurrence or Even, Improving product, and Supposing. Analysis of the data used is the N-Gain analysis and paired t-test. The results showed the C3PDR Learning Model influenced the increase of conceptual understanding and the creative thinking skills of senior high school students on sound waves topic. This is indicated by 1) N-Gain of conceptual understanding was 0,76 in the high category, 2) N-Gain of creative thinking skills was 0.51 in the moderate category, 3) A significant difference between students' conceptual understanding and 4) the students' creative thinking skills before and after the C3PDR Learning Model was applied, marked with p mode <0.05.